FILM BERNUANSA BUDAYA ACEH SEBAGAI MEDIA DAKWAH (ANALISIS SEMIOTIKA PADA FILM DOKUMENTER DALAE DAN FILM DOKUMENTER BEUT BA’DA MEUGREB) - Mahlil, Mahlil (JURNAL AL-IJTIMAIYYAH, 2020)
The present, film is not only limited to the delivery of information, but also as a medium of entertainment, education, criticism, and so on, including as a dakwah media. The culture of Aceh has close links with Islamic elements and is a reflection of the lifestyle of the Acehnese people, because the culture of Aceh is inseparable from the scient system that is related to society. Culture is a legacy in the form of behavior, attitudes, habits, and norms in the form of verbal symbols and non-verbal messages that are practiced by humans in their daily lives. This study uses qualitative research with a semiotic analysis approach and interpretative methods. The purpose of this study was to analyze the signs and meanings associated with the values of da'wah in the documentary film dalae and beut ba'da meugreb. The results showed that the message of da'wah seen in the film dalae and beut ba'da meugreb contained many positive values because it contained an Islamic culture. The dakwah values contained in the film dalae can be seen in the dalail khairat (dalae) activities, also when the main subject invites meunasah priest to revive dalae activity, and the participants take seriously do it. Whith the shalawat to the Prophet, advice and prayers. In the villages, activities are carried out seriously, but in urban areas dalae activities have weakened and faded. Because many young men are negligent. Whereas the values of dakwah seen in the film Beut Ba'da Meugreb are when a young man search the cause of Beut Ba'da Meugreb is no more in his village. In general, the two films tell about the phenomenon of shifting religious values in Aceh. The aim of the two films is that the activities in dalae and beut ba'da meugreb are more advanced, more vibrant, and sustainable. In closing, the film dalae and beut ba'da meugreb contain the values of dakwah that need to be preserved in the future and it is hoped that their activities will be sustainable and better in dakwah Islam in Aceh.Keywords: Film, Acehnese Culture, Dalae, and Beut Ba’da Meugreb.